CELEBRATION OF A DECADE OF JME - Zulkardi Zulkardi (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2019)
Journal on Mathematics Education (JME), formerly called Indonesian Mathematical Society Journal on Mathematics Education (IndoMS-JME), is the first international journal on mathematics education in Indonesia. The primary goal of the journal is to support and facilitate mathematics educators and researchers either from Indonesia or other countries to publish their works in mathematics education. In 2010, Professor Zulkardi, the vice president of the Indonesian Mathematical Society (IndoMS) as well as a mathematics educator from the Universitas Sriwijaya started the JME. Professor Widodo, the president of IndoMS at that time, launched the first volume of the JME at the opening of National Conference on Mathematics in Universitas Negeri Manado, June 30th, 2010. This editorial focuses not only on the celebration of the achievements and challenges of JME but also the process of the growth of the JME from a local journal, national, and then to be a reputable international journal.First, as a local journal, JME started with only five articles in the first volume. Luckily, an international expert in mathematics education wrote and published their ideas. Lee Peng Yee, a professor at the National Institute of Education (NIE) Singapore, wrote an article about how to design a mathematics curriculum. Also, Professor Sembiring, from the Institut Teknologi Bandung, wrote about the history of Realistic Mathematics Education in Indonesia. Later on, many authors from various countries published their papers in the next volumes. Some of the well-known researchers in mathematics education have contributed to the JME, such as Professor Berinderjeet Kaur from Singapore; Kaye Stacey, Bardini, and Tom Lowrie from Australia; Christa Kaune and Elmar Cohort from Germany; Edyta Nowinska from Poland; Koeno Gravemeijer, Maarten Dolk, Dolly and Frans van Gallen from the Netherlands. The other authors are from the Kingdom of Saudi Arabia, Brunei Darussalam, Indonesia, Turkey, Ghana, United States, and Taiwan. Second, the JME is nationally accredited by the Ministry of Research, Technology, and Higher Education since September 2015. A year before, the Directory Open Access Journal (DOAJ) and ERIC databases started to index the articles from the JME.Finally, after waiting for 20 months since the application submitted, the JME is accepted for the Scopus inclusion since September 2018, addressing the JME as one of the reputable international journals from Indonesia. After another three months, Elsevier agreed to cover all articles since volume 9.1 in the Scopus database. In this celebration moment, as the editor in chief, I would like to say thank you very much to all local staffs, managing editors, reviewers, as well as editorial board members either from abroad or Indonesia who have done excellent work in making JME well known and internationally recognized. Starting from January 2019, JME publishes three editions on each volume.Finally, in the future, JME has an effort to improve the quality of publication both management and the content of the articles. Also, JME has a task to fulfil the requirements to be indexed in the Web of Science. Of course, this is not an easy task, especially for JME team.